2021
DOI: 10.1177/10648046211018541
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Acceptability of Smart Eyewear for Plot Diagnosis Activity in Agriculture

Abstract: Smart glasses could meet the plot diagnosis activity needs in agriculture. Therefore, their acceptability must be evaluated. We conducted user tests with agricultural advisors to assess perceived comfort and user experience. The participants reported comfort issues like and harm problems, and obstruction or disturbance of the visual field. Objective and subjective evaluations were poorer when the device was used in voice mode compared with buttons. Despite these limitations, the participants mentioned the pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(45 reference statements)
0
0
0
Order By: Relevance
“…One of the first such studies developed a system for displaying NDVI and geo-referenced yield data on vineyards [14]. Other applications have involved the implementation of AR systems for tractor driving assistance [15], the control of the operation of two autonomous agricultural machines using an AR device [16], and the use of a mobile-based AR application for Abalone growth monitoring [17], to promote sustainable development in hydroponic cultivation, [18] and for plot diagnosis activities in vineyards [19]. The benefits of the adoption of SGs for AR in the livestock sector were shown in recent studies testing systems to support operators in farm management [20], for the visualization of the production data of dairy sheep in the milking parlor [21], for monitoring of the ventilation system in the barn [22] and for the visualization of specific animal data from sheep farms [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the first such studies developed a system for displaying NDVI and geo-referenced yield data on vineyards [14]. Other applications have involved the implementation of AR systems for tractor driving assistance [15], the control of the operation of two autonomous agricultural machines using an AR device [16], and the use of a mobile-based AR application for Abalone growth monitoring [17], to promote sustainable development in hydroponic cultivation, [18] and for plot diagnosis activities in vineyards [19]. The benefits of the adoption of SGs for AR in the livestock sector were shown in recent studies testing systems to support operators in farm management [20], for the visualization of the production data of dairy sheep in the milking parlor [21], for monitoring of the ventilation system in the barn [22] and for the visualization of specific animal data from sheep farms [23].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is significant to evaluate whether these devices and the on-farm activities might be combined. In fact, recent studies have confirmed that these technologies represent a promising solution in the digitalization of modern farms [19][20][21]. Specifically, SGs require further investigation to support the wider use of these systems.…”
Section: Introductionmentioning
confidence: 99%